2015
DOI: 10.1002/adsc.201500723
|View full text |Cite
|
Sign up to set email alerts
|

Iridium‐Catalyzed Enantioselective Hydrogenation of β,β‐Disubstituted Nitroalkenes

Abstract: Ah ighly efficient, iridium-catalyzed, enantioselective hydrogenation of b,b-disubstituted nitroalkenesh as been developed. Using ac omplex consisting of iridium and (S,S)-f-spiroPhos as the catalyst, av ariety of b,b-disubstituted nitroalkenes were successfully hydrogenated to the corresponding chiral nitroalkanes with excellent enantioselectivities (up to 98% ee)a nd high turnover numbers (TON = 1000).Keywords: asymmetric catalysis; enantioselectivity; hydrogenation;i ridium;n itroalkenes Asymmetric hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Recently, Ding and co-workers developed a Rh catalyst containing a chiral monodentate phosphine (SPO) ligand and an achiral Ph 3 P ligand, which exhibited excellent enantioselectivity for the asymmetric hydrogenation of β,β-diarylacrylic acids and β-CF 3 -substituted acrylic acids. , Whereas in most of the reported cases of the asymmetric hydrogenation of unsaturated acrylic acids, a base additive (NEt 3 or morpholine) was required to achieve high efficiency and enantioselectivity. Accordingly, the development of more efficient catalysts for the asymmetric hydrogenation of β,β-disubstituted acrylic acids is highly desirable. Inspired by the excellent performance of the chiral diphosphine ligand f-spiroPhos in Rh- or Ir-catalyzed asymmetric hydrogenations of α,β-unsaturated nitriles and nitroolefins, we evaluated this ligand for the hydrogenation of β,β-disubstituted unsaturated acrylic acids, including sterically similar β,β-diaryl unsaturated acrylic acids, and found that its Rh complex showed excellent enantioselectivities (up to 99.3% ee) under mild reaction conditions without any additive (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ding and co-workers developed a Rh catalyst containing a chiral monodentate phosphine (SPO) ligand and an achiral Ph 3 P ligand, which exhibited excellent enantioselectivity for the asymmetric hydrogenation of β,β-diarylacrylic acids and β-CF 3 -substituted acrylic acids. , Whereas in most of the reported cases of the asymmetric hydrogenation of unsaturated acrylic acids, a base additive (NEt 3 or morpholine) was required to achieve high efficiency and enantioselectivity. Accordingly, the development of more efficient catalysts for the asymmetric hydrogenation of β,β-disubstituted acrylic acids is highly desirable. Inspired by the excellent performance of the chiral diphosphine ligand f-spiroPhos in Rh- or Ir-catalyzed asymmetric hydrogenations of α,β-unsaturated nitriles and nitroolefins, we evaluated this ligand for the hydrogenation of β,β-disubstituted unsaturated acrylic acids, including sterically similar β,β-diaryl unsaturated acrylic acids, and found that its Rh complex showed excellent enantioselectivities (up to 99.3% ee) under mild reaction conditions without any additive (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Related chemistry, dealing with addition to keto analogues of imine 7, is presented in Scheme 4. In this case, the reactions between ketimines (R)-13 and various Ar-Li derivatives occurred with very high yields and diastereoselectivity, [29] allowing preparation of interesting amines 15 and amino acids 16, each containing a quaternary stereogenic carbon atom. The generality of these addition reactions could be extended to include CHF 2 , CClF 2 , and perfluoroalkyl groups, as well as alkyl-Li reagents.…”
Section: Additions Of C(sp 2 )-M Nucleophilesmentioning
confidence: 98%
“…[26,27] The absolute stereochemistry of the newly created stereogenic center in the additions of (S)-7 was determined to be S; however, the mechanistic explanation for the preferential for-mation of diastereomers 11 was rather vague, [27] with a reference to a "non-chelated transition-state model". [28] Under the standard conditions [29] compounds 11 were easily deprotected to afford the target CF 3 -amines 12.…”
Section: Additions Of C(sp 2 )-M Nucleophilesmentioning
confidence: 99%
“…10 Although there are some successful asymmetry syntheses of (S)-ibuprofen reported, the main enantioselective synthetic approaches include hydrogenation of b,b-disubstituted nitroalkenes, 11 hydrocarboxylation of olefins, 12 Grignard cross-coupling of vinyl bromide, 13 protonation of silyl enol ethers, 14 iron-bisphosphine-catalyzed cross-coupling of a-chloropropanoate, 2 hydrogenation of aldehydes, 15 and hydrocyanation of vinylarenes, 16 more efficient and convenient asymmetric syntheses of this drug still remain highly desirable.…”
Section: Introductionmentioning
confidence: 99%